2013
DOI: 10.1029/2012jg001978
|View full text |Cite
|
Sign up to set email alerts
|

Recent acceleration of carbon accumulation in a boreal peatland, south central Alaska

Abstract: [1] The ongoing warming in high-latitude regions may be causing rapid changes in the structure and functioning of terrestrial ecosystems. Of particular concern is the fate of belowground soil organic carbon stored in peat-accumulating wetlands, as these large carbon pools are sensitive to temperature and moisture conditions. Despite their important role in the global carbon cycle, considerable uncertainty remains over the carbon balance of northern peatlands in a changing climate. Here we examine the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 103 publications
(161 reference statements)
9
107
1
Order By: Relevance
“…Other studies indicated that climate change can further diminish C sequestration by promoting the growth of vascular plants which, in turn, depress the productivity of peat mosses (Breeuwer et al, 2009;Bragazza et al, 2013). In contrast to these studies, Loisel and Yu (2013) and Charman et al (2013) indicated that the C accumulation rate of many northern peatlands could increase in response to a warmer climate in the future, as long as moisture is not a limiting factor. These examples illustrate the ongoing debate on the fate of C in peatlands in response to climate change.…”
Section: Introductionmentioning
confidence: 42%
“…Other studies indicated that climate change can further diminish C sequestration by promoting the growth of vascular plants which, in turn, depress the productivity of peat mosses (Breeuwer et al, 2009;Bragazza et al, 2013). In contrast to these studies, Loisel and Yu (2013) and Charman et al (2013) indicated that the C accumulation rate of many northern peatlands could increase in response to a warmer climate in the future, as long as moisture is not a limiting factor. These examples illustrate the ongoing debate on the fate of C in peatlands in response to climate change.…”
Section: Introductionmentioning
confidence: 42%
“…A lack of Sphagnum remains observed in the plant macrofossil samples when Sphagnum spores are present may suggest high decomposition rates causing the loss of preservation of plant material at these depths (below 65 cm depth), also supported by high levels of UOM (Loisel and Yu, 2013).…”
Section: Suggestions For Future Workmentioning
confidence: 99%
“…The carbon balance of peatlands is determined by the joint effect of frequently changing biogeochemical processes of photosynthesis and respiration, so the peat carbon sequestration often shows great fluctuation over a wide range of timescales. Peat core data indicated that carbon accumulation rate varies over millennial (Frolking and Roulet, 2007;Yu et al, 2010), centennial (Craft and Richardson, 1998;Malmer and Wall en, 2004;Ali et al, 2008) and decadal timescales (Craft and Richardson, 1998;Wieder, 2001;Gao et al, 2010;Loisel and Yu, 2013), which can be attributable to many factors, such as climate change (Ise et al, 2008;Cai et al, 2010;Yu, 2011), geological and human disturbances (Yu et al, 2010;Hooijer et al, 2010), landscape morphology (Belyea and Baird, 2006) and self-regulation mechanisms (Wu, 2012). Overall, climate change, which is ubiquitous in the whole world, turns out to be a crucial element in determining carbon accumulation rate of peatlands over different timescales (Friedlingstein et al, 2006;Cai et al, 2010;Yu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because we did not have enough data to model the decay coefficient (a) to reconstruct accurate NCU for the other sites, we estimated their NCU by assuming that they had the same decay coefficient (a) with Huahu peat core. The remaining modern peat masses after 25, 50 and100 yr decomposition were assumed to be equivalent to 60%, 44.4% and 29.6%, respectively, of the initial mass (Loisel and Yu, 2013). Assuming the surface peat decay rate of QTP peatlands as 0.0244 yr À1 reported by Loisel and Yu (2013), we used the recent C accumulation rate obtained from peat cores, which represents the remaining C mass after 25 yr decomposition, to back calculate the initial peat C mass.…”
mentioning
confidence: 99%